Sasi in Kei Island: Transformation of Coastal Resources Managementby Community in Tanimbar Kei Island, Maluku, Indonesia - Anes D. Jayanti; Katsuya Osozawa (Jurnal Perikanan Universitas Gadjah Mada, 2014)
Sasi is a local Indonesian traditional resources management system, which manages responsibilities and marine tenure rights in Maluku. Dwellers have been using this system for over 400 years and it consists of spatial and temporal prohibitions on harvesting crops. Sasi was viewed as an appropriate method to achieve harmony between man and nature. It has been noted that sasi has been affected by many factors. These factors have allowed sasi to exist in some areas and become extinct in other areas, which are very essential indicators when considering how to effectively achieve sustainability. Studyingthe factors that transformedsasi, understanding villagers’ perception and reaction to sasi’s transformation and how they planned to sustainably manage their natural resources will support the community based management model for eastern Indonesia. This research was conducted in Tanimbar Kei Island, which actively follows the rules of sasi. To determine the effectiveness of sasi in terms of social and environmental sustainability, demographic, social, politic and economic factors were studied. This study used the triangulation method, which consists of literature studies, area studies, in-depth interviews and questionnaires. The data was analyzed with qualitative analysis, institutional analysis and sustainability analysis. The results show a change in perceptions and community institutions. The dominant factor affecting sasi is the political aspect, especially concerning policy autonomy and assistance from NGOs. The community trust in sasi and other community members ensures that sasi’s transformation does not cause it to lose its identity and function.